Study of the Performance in the Local Electrical Distribution System - Ginko Georgiev, Silviya Letskovska, Kamen Seymenliyski and Pavlik Rahnev (Journal of Information & Systems Management, 2022)
The calculation of the Coefficient of Voltage Non-sinusiadility on the Bus of Substation is a significant issue. We have presented the results of the local electrical distribution system of a company in this paper. We have also performed the experimental results. We have assessed the reasons for the determining the damages and proposed many solutions to fix the technical as well as the economic decisions for the issues.